An empirical analysis of how artificial intelligence development influences the adjustment of human capital structure - Dong, Zixuan; Abd Aziz, Mohd Faiq; Wang, Yan (Elsevier, 2025)
This article, utilizing a dataset spanning Chinese listed companies from 2011 to 2022, delves into the implications of advancements in artificial intelligence on the transformation of corporate human capital structures. The research uncovers that the progression of AI contributes to the refinement of human capital within firms, evident in the heightened proportion of skilled labor and the enhancement of functional configurations. Importantly, these effects display notable disparities between state-owned enterprises (SOEs) and private enterprises (PEs). Additionally, the study highlights the mediatory function of enterprise total factor productivity in the relationship between AI development and human capital structural adjustments.